2022
DOI: 10.1177/02698811211069113
|View full text |Cite
|
Sign up to set email alerts
|

LSD and creativity: Increased novelty and symbolic thinking, decreased utility and convergent thinking

Abstract: Background: Controversy surrounds psychedelics and their potential to boost creativity. To date, psychedelic studies lack a uniform conceptualization of creativity and methodologically rigorous designs. Aims: This study aimed at addressing previous issues by examining the effects of lysergic acid diethylamide (LSD) on creativity using multimodal tasks and multidimensional approaches. Methods: In a randomized, double-blind, placebo-controlled, crossover study, 24 healthy volunteers received 50 μg of LSD or inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Consumption of psilocybin truffles has been found to yield distinct effects on measures of creativity as part of the acute and persisting effects of the substance, increasing ratings of divergent thinking the morning following usage, and enhancing convergent thinking a week following usage (Mason et al, 2019). A moderate dose of psilocybin has been associated with spontaneous creative insights, while decreasing deliberate task-based creativity during the acute experience, with an increase in the number of novel ideas at seven days post experience reported (Mason et al, 2021), while a moderate (50 µg) dose of LSD has also been found to increase originality and novelty in thinking (Wießner et al, 2021b). One study reported an enhancement of convergent thinking sustained for four weeks following an ayahuasca experience (Uthaug et al, 2018) while another assessed participants engaging in several ayahuasca sessions in a ritual setting, and found that ayahuasca users exhibited increased originality on a standardised test of creative thinking, sustained at two week follow-up post experience (Frecska et al, 2012).…”
Section: Effects Of Psychedelics On Cognitive Processes Relevant To C...mentioning
confidence: 98%
See 3 more Smart Citations
“…Consumption of psilocybin truffles has been found to yield distinct effects on measures of creativity as part of the acute and persisting effects of the substance, increasing ratings of divergent thinking the morning following usage, and enhancing convergent thinking a week following usage (Mason et al, 2019). A moderate dose of psilocybin has been associated with spontaneous creative insights, while decreasing deliberate task-based creativity during the acute experience, with an increase in the number of novel ideas at seven days post experience reported (Mason et al, 2021), while a moderate (50 µg) dose of LSD has also been found to increase originality and novelty in thinking (Wießner et al, 2021b). One study reported an enhancement of convergent thinking sustained for four weeks following an ayahuasca experience (Uthaug et al, 2018) while another assessed participants engaging in several ayahuasca sessions in a ritual setting, and found that ayahuasca users exhibited increased originality on a standardised test of creative thinking, sustained at two week follow-up post experience (Frecska et al, 2012).…”
Section: Effects Of Psychedelics On Cognitive Processes Relevant To C...mentioning
confidence: 98%
“…This suggests that while there may be gains in some forms of creative thinking under a psychedelic, there are likely to be accompanying deficits in analytical thinking. This suggests that the psychedelic state may contribute to aspects of creative generation, but not to creative evaluation (Girn et al, 2020;Wießner et al, 2021b). The illumination phase of the creative process is associated with loose, freely associative and non-logical thought and highly subjective ideation or primary process thinking, this being a shared feature of the psychedelic (Kraehenmann et al, 2017), dream (Livingston & Levin, 1991) and hypnagogic (Mavromatis, 1987) states.…”
Section: Altered States and Creativitymentioning
confidence: 99%
See 2 more Smart Citations
“…Wießner et al (2022) employed a double-blind, placebo-controlled, crossover study design with 50 μg of LSD versus inactive placebo to examine the effects of LSD on creativity in healthy volunteers. A creative battery task was administered around peak drug effects.…”
mentioning
confidence: 99%